ANALYSIS OF THE INFLUENCE OF FISCAL POLICY ON ECONOMIC GROWTH WITH INVESTMENT AS A MODERATING VARIABLE IN INDONESIA - Tohap Parulian; A. Mahendra; Witya Shalini (RADJA PUBLIKA, 2024)
This research aims to know the influence of tax and government expenditure on economic growth with investment as a moderating variable in Indonesia. The population in this research is Indonesia, and 24 of them were selected to be the samples for this research through a purposive sampling technique. This research uses multiple regression analysis techniques. This study's data type is secondary data, consisting of tax and government expenditure for economic growth for 2000-2024. This research showed that tax and government expenditures partially significantly affect economic growth in Indonesia. At the same time, simultaneously (f-test), Tax and Government Expenditure significantly affect the variables of Economic Growth. The investments cannot moderate the relationship between Tax and Government Expenditure on Economic Growth.